ISLAMIC WORK ETHIC : (Kajian Tafsir Tematik Tentang Integritas dan Ketenagakerjaan) - Alamsyah Halim; Achmad Abu Bakar; Mardan (Rausyan Fikr: Jurnal Ilmu Studi Ushuluddin dan Filsafat, 2022)
This article proposes terms or terms that become benchmarks and entrances in finding similarities in intent with work ethic, either through words, phrases, clauses or sentences that have meaning with work ethic. Through this media, terms related to work ethic in the Qur'an will be found. The purpose of this study is to reveal the meaning of work ethic and its terms in the Qur'an. This research uses descriptive qualitative method through the design of the thematic study research type. The technique of data collection is done by literature study. The results of the study found terms in the Qur'an that contain the same meaning with work ethic, including: the terms al-'amal (al-salih), al-ibtiga', al-kasb, al-itqan, al-ihsan, al-birr, al-ta'awun, al-jihad, istibaq al-khairat, ita al-mal, tazyin al-hubb al -syahawat min al-qanatir al-muqantarah, al-wafa' bi al 'uqud, and miras al-ard.